PERSEPSI MAHASISWA DALAM MEMVALIDASI BUKTI MATEMATIS - Matitaputty, Christi (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2020)
This study aims to describe the perceptions of prospective students in the first year in validating mathematical proof. This student's perception is discussed based on the answers given to the proof of a theorem. This research is a qualitative research. The subjects in this study were three students from the second semester mathematics education study program at a university in East Java. Research subjects were chosen deliberately with the following considerations: prospective teacher students who use examples in making mathematical proof and good communication skills make research can facilitate students' perceptions in writing mathematical proof. The results showed that students had perceptions about who gave several examples so that the proof was called valid, one example of denying it could prove it was invalid and using formal proof that proved it could be proven valid